PENGARUH PENGGUNAAN BAHASA INDONESIA DALAM KEHIDUPAN SEHARI-HARI TERHADAP BAHASA SUNDA DALAM MASYARAKAT DI JAWA BARAT - Erwin Rada Damanik (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to determine the intensity of the use of Indonesian and how much influence the intensity of the use of Indonesian has on the local community, namely West Java. Some of the influences or impacts of using Indonesian on regional languages (Sundanese/West Java). The positive impact is: the Indonesian language has a lot of vocabulary, as the cultural wealth of the Indonesian people, as an identity and characteristic of a tribe and region, and creates intimacy in communication. There are so many regional languages from each region, one with another, for example, for the West Java region, Sundanese has Sundanese as the regional language, while Medan has Batak language as the regional language. This regional language can distinguish one region from another. The regional language for its speakers has been ingrained because it is used every day. With the existence of regional languages, the Indonesian people are bilingual (bilingual) people who master more than one language, namely regional languages, Indonesian, and foreign languages.